2006
DOI: 10.1080/03009740500343260
|View full text |Cite
|
Sign up to set email alerts
|

Disability and health‐related quality of life among patients with rheumatoid arthritis: association with radiographic joint damage, disease activity, pain, and depressive symptoms

Abstract: Daily RA practice needs to be broadened by regular assessment of disease burden from the patients' perspectives. Patient-reported measures, such as disability or HRQoL, should be incorporated for monitoring health outcomes of individual patients and for initiating and evaluating therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 32 publications
6
42
0
8
Order By: Relevance
“…28 Rupp and his colleagues who studied on disability and health-related quality of life, pointed to RA as an effective factor interferes with normal daily activities and sleep. 29 Also individual character is one of those factors which can be aligned with sleep rhythm and rest, also can be effective on QOL. For instance, results showed that age as an individual character can influence the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…28 Rupp and his colleagues who studied on disability and health-related quality of life, pointed to RA as an effective factor interferes with normal daily activities and sleep. 29 Also individual character is one of those factors which can be aligned with sleep rhythm and rest, also can be effective on QOL. For instance, results showed that age as an individual character can influence the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…www.kan.or.kr ity of life, HRQoL)의 저하를 초래한다 (Rupp, Boshuizen, Dinant, Jacobi, & van den Bos, 2006). 최근 10년간 류마티스 관절염환자의 건강관련 삶의 질의 관련요 인들을 보고한 연구들은 다음과 같다.…”
unclassified
“…성별 (Oh, 2000), 연령 (Jakobsson & Hallberg, 2002;Suh, Kim, & Roh, 2002), 교육수준 (Oh), 직업 (Lu, Lin, Lin, & Lin, 2008;Nichol & Zhang, 2005) 등 인구학적 요인들과 관 절염 유병기간 (Oh;Park, Nam, & Baek, 2000), 통증 (Benitha & Tikly, 2007;Jakobsson & Hallberg;Lu et al;Rupp et al, 2006), 일상 생활 수행능력 장애 (Benitha & Tikly;Haroon, Aggarwal, Lawrence, Agarwal, & Misra, 2007;Jakobsson & Hallberg;Lu et al;Oh), 질병활성 도 (Benitha & Tikly; Haroon et al; Jakobsson & Hallberg; Lu et al; Rupp et al) 등 질병관련 역학적, 신체적 요인들이 주요 영향요인으로 보 고되었다. 이외에 우울 (Kojima et al, 2009;Rupp et al;Suh et al;Tander et al, 2008), 사회적 지지 (Kojima et al;Oh;Park & Park, 2000;Suh et al), 자기효능 (Park, 1999 …”
unclassified
“…Thus, the main treatment aims are to improve QoL and minimize disease complications (21). In RA cases, the disease activity is not sufficient for the exact detection of the effects of RA on QoL (22). Evaluating and measuring QoL in the patients with RA is the most comprehensive method to assess disease effects and monitor response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…AUASI questionnaire includes seven questions to query the presence of a possible irritative (frequency, urgency, and nocturia) and obstructive (incomplete emptying, decrease in flow rate, and straining) urinary symptoms. A scoring system was utilized to classify the degree of the symptoms as mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The final item of the AUASI form investigates the impact of urinary symptoms on QoL, and this entity is scored between 0 and 6 (10).…”
Section: Methodsmentioning
confidence: 99%